PENGARUH NARKOBA TERHADAP KENAKALAN REMAJA DI SULAWESI TENGAH - Syafii, Ahmad (MEDIA LITBANG SULTENG, 2009)
The youth in the modern era was exceedly beyond the normal situation. There were many chindren under teens has already exposured with narcotic and psychotropic. Narcotic and psychotropic is the substance if intake by body it will effect particularly to the central nerve so if there were abuse it will couse the physical disturbance, physic and social function. There for the government issued the regulation of drug abuse namely UU No.5 year 1997 about Psychotropic and UU No.22 year 1997 about Narcotic. In the Central Sulawesi, the drug abuse has been used widely in the community particularly to the youth that curious to know and just want to try as the modern life style. Narcotic and psychotropic is the critical and complicated issue that can not be completed only by one part. Because the narcotic and psychotropic was not only the individual problem but also involved old part both in the government, non alignment organization and local community. The prevention of drug abusement is the effort conducted towards some influential factor both directly and indirectly to change the belief, manner and the behavior of youth towards the use of narcotic and psychotropic.